2017
DOI: 10.5267/j.ijiec.2017.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and optimization for CSDGB filling system of a beverage plant using particle swarm optimization

Abstract: The paper deals with the performance analysis and optimization for Carbonated Soft Drink Glass Bottle (CSDGB) filling system of a beverage plant using Particle Swarm Optimization (PSO) approach. The CSDGB system consists of seven main subsystems arranged in series namely Uncaser, Bottle Washer, Electronic Inspection Station, Filling Machine, Crowner, Coding Machine and Case Packer. Considering exponential distribution for probable failures and repairs, mathematical modeling is performed using Markov Approach (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…S e t -1 : 1 = 0.02 , 2 = 0.05, 3 = 0.03 , 4 = 0.023, 1 = 0.61 , 2 = 0.8, 3 = 0.72 , 4 = 0.45 the numerical values of fuzzy availability and profit function have been obtained by considering different values of coverage (30) dP 30 (t) dt + 1 P 30 (t) = 2 1 (1 − )P 9 (t)…”
Section: Numerical and Graphical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S e t -1 : 1 = 0.02 , 2 = 0.05, 3 = 0.03 , 4 = 0.023, 1 = 0.61 , 2 = 0.8, 3 = 0.72 , 4 = 0.45 the numerical values of fuzzy availability and profit function have been obtained by considering different values of coverage (30) dP 30 (t) dt + 1 P 30 (t) = 2 1 (1 − )P 9 (t)…”
Section: Numerical and Graphical Resultsmentioning
confidence: 99%
“…Aggarwal et al [29] formulated a mathematical model and obtained the results for reliability of the serial processes in feeding system. Kumar and Tewari [30] used PSO technique for performance analysis and optimization of CSDGB filling system of a beverage plant. Kadyan and Kumar [31] analyzed the availability based operational behavior of B-Pan crystallization system in the sugar industry.…”
Section: Introductionmentioning
confidence: 99%
“…Malik & Tewari, (2020) developed a mathematical model to improve performance of a coal crushing unit of thermal power plant using PSO. Kumar et al (2020) performed SSA analysis of waste gases recovery system by applying MM. It was found that availability value is very low, and reason of this is failure of boiler tube.…”
Section: Introductionmentioning
confidence: 99%
“…Haitang et al [2] analysed the reliability of CAM on Gear Plate of D Type Knotter. Kumar and Tewari [3] conducted the optimization of a filling system at a beverage plant through the Particle Swarm Optimization technique. Kumar et al [4] studied the impact of hot-cold redundancy of the pumps on the availability level of a thermal plant using the Markov technique.…”
Section: Introductionmentioning
confidence: 99%